Sugarcane Trash Management for residue recycling and higher productivity - Gadge, S K; Powar, M S; Bhor, D B; Jadhav, Vilas (Indian Farming, 2017)
Sugarcane farmers are also happy by sugarcane trash management since they get an additional income of Rupees 15,000/ ha due to increase in yield of sugarcane @ 6 MT/ha. The effect of sugarcane trash management is such that the entire village has stopped burning of trash and around 40% people of Tasgaon and Palus block of Sangli district are now adopting the technology of sugarcane trash management.